Components of customer retention strategy in mobile telephone industry in Malaysia: structural equation modeling (Sem) - Othman, Anwar Hasan Abdullah; Is’ haq, Amandu Yassin (Global Journals Inc. (USA), 2015)
This paper seeks to confirm underlying components of Customer Retention Strategy in mobile phone services. The study adopted structural equation modeling to analyze the factors that constitute customer retention strategy. The study utilized 250 valid questionnaires administered to respondents at the International Islamic University Malaysia, Kuala Lumpur. Random sampling with the basic criteria of respondents being 18 years and above using mobile phone services was adopted. The respondents included University staff academic and non- academic, students of various levels ranging from bachelor’s, through master’s and doctor of philosophy in various faculties and departments. The study found out that relational investment, solidarity, customer trust and satisfaction are key components of Customer Retention Strategy. The components explain 62% variance in the Customer Retention Strategy.